Identifikasi Budaya Lokal Wilayah Napu Sebagai Sumber Belajar di SD Negeri Winowanga - aswinda; Herlina, Herlina (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2022)
This study was conducted to emphasize the importance of preserving local culture through elementary education as a means of instilling identity, character, and pride in students’ regional heritage. The lack of integration of local culture into learning at SDN Winowanga motivated this research. The study aims to identify cultural elements in the Napu region that can be utilized as learning resources and to describe how these elements can be integrated into elementary school learning. This research used a qualitative approach with a phenomenological design. The participants included the school principal, fifth-grade teachers, students, and community leaders in the Napu area. Data were collected through observations, interviews, literature studies, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing.The findings reveal that local Napu cultural elements with educational potential include the Masalo/Dengki traditional dance, the Tambi traditional house, and the Napu regional language. These cultural aspects hold strong educational, social, and historical values relevant to thematic learning in elementary schools. The integration of these cultural elements is implemented through PPKn and SBdP subjects, as well as extracurricular art activities. The study concludes that incorporating local culture as a learning resource can enrich learning content, strengthen students’ character, and foster appreciation for their cultural heritage. It is recommended that schools develop curricula based on local culture and enhance teachers’ competence in implementing culture-based learning practices.